2019
DOI: 10.2147/jpr.s210471
|View full text |Cite
|
Sign up to set email alerts
|

<p>Assessing the reporting quality in randomized controlled trials of acupuncture for postherpetic neuralgia using the CONSORT statement and STRICTA guidelines</p>

Abstract: Background This study evaluates the reporting quality of randomized controlled trials (RCTs) on acupuncture use for the treatment of postherpetic neuralgia and explores related factors. Methods The following six databases PubMed, Embase, Cochrane Library, VIP, CNKI, and SinoMed, were systematically searched from their inception to December 2018. RCTs using acupuncture as an intervention for postherpetic neuralgia were selected and incorporated in this study. The reporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 31 publications
6
12
1
Order By: Relevance
“…Our findings are similar to those previously reported, in which the authors found the reporting in acupuncture RCTs for a broad range of topics was generally poor when CON-SORT and STRICTA were used to assess the reporting quality [12][13][14][23][24][25][26][27][28][29][30][31]. Additionally, several studies have shown the overall high rates of RCTs at unclear and high RoB on acupuncture, which are consistent with our findings [16,20,32].…”
Section: Plos Onesupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are similar to those previously reported, in which the authors found the reporting in acupuncture RCTs for a broad range of topics was generally poor when CON-SORT and STRICTA were used to assess the reporting quality [12][13][14][23][24][25][26][27][28][29][30][31]. Additionally, several studies have shown the overall high rates of RCTs at unclear and high RoB on acupuncture, which are consistent with our findings [16,20,32].…”
Section: Plos Onesupporting
confidence: 91%
“…Many studies have assessed the RoB or reporting quality in acupuncture RCTs, but they are restricted to the number of RCTs included, specific topics, journals, or countries [12][13][14][15][16][17]. As far as we know, there has not been an article that assesses the RoB of acupuncture RCTs from the inception of research.…”
Section: Introductionmentioning
confidence: 99%
“…Using the CONSORT explanation and elaboration statement for abstracts of parallel group randomized trials by Moher et al [4] and previous reports [ 5 , 14 ], two reviewers worked independently (DGW and YGZ) to make a judgment on whether an item in the RCT abstract was adequately reported. These two reviewers were calibrated through rounds of 10 randomly selected abstracts until strong agreement (Cohen's κ statistic ≥0.90) was reached.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, only 12 items had an optimal reporting rate (reported in over 70% of trials) in our study. Some studies on RCTs of TCM treatments hold the same results, and the number of items with an optimal reporting rate ranged from 10 to 16 [ 15 17 ]. In summary, most included RCTs in this study did not strictly comply with the CONSORT-CHM formulas 2017, and the reporting quality of 144 RCTs was suboptimal.…”
Section: Discussionmentioning
confidence: 99%